2013
DOI: 10.1074/jbc.m112.444810
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Normal and Collagen IX Null Mouse Cartilage Reveals Altered Extracellular Matrix Composition and Novel Components of the Collagen IX Interactome

Abstract: Background: Collagen IX is an integral cartilage extracellular matrix component important in skeletal development and joint function. Results: Proteomic analysis and validation studies revealed novel alterations in collagen IX null cartilage. Conclusion: Matrilin-4, collagen XII, thrombospondin-4, fibronectin, ␤ig-h3, and epiphycan are components of the in vivo collagen IX interactome. Significance: We applied a proteomics approach to advance our understanding of collagen IX ablation in cartilage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 53 publications
5
46
0
Order By: Relevance
“…We could previously show that collagen IX ablation was associated with dramatically reduced COMP and matrilin-3 in cartilage, consistent with known interactions [9], and therefore analyzed their protein expression in mimic-and inhibitor-transfected cells. Neither protein represents a direct target of the miR-26a, but both were significantly reduced in miR-26a mimic-transfected cells (Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…We could previously show that collagen IX ablation was associated with dramatically reduced COMP and matrilin-3 in cartilage, consistent with known interactions [9], and therefore analyzed their protein expression in mimic-and inhibitor-transfected cells. Neither protein represents a direct target of the miR-26a, but both were significantly reduced in miR-26a mimic-transfected cells (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Matrilin-3 and COMP are not direct targets of the miR-26a, but collagen IX interacts with COMP and matrilin-3 to stabilize the fibrillar and extrafibrillar compartment of the cartilage [8,15,16]. Ablation of collagen IX decreased matrilin-3 and COMP [9,15,16]. Therefore, decreased collagen IX abundance in PECs after miR26a transfection could be the main reason for the significant reduction in matrilin-3 and COMP.…”
Section: Discussionmentioning
confidence: 93%
“…Collagen IX can combine with tissue inhibitors of matrix metalloproteinases, growth factors, and cartilage cell-surface receptors, and plays an important role in protecting articular cartilage and maintaining its internal stability (Parsons et al, 2011;Brachvogel et al, 2013). It has been reported that mutations in collagen IX genes are associated with the development of skeletal abnormalities (Posey et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has shown that mutations in collagen IX genes can cause variation in bone marrow hypoplasia, and might be the molecular biological basis of articular cartilagerelated diseases, the risk of which previous studies have associated with COL9A1 expression (Liu et al, 2011;Brachvogel et al, 2013). Polymorphisms in this gene can alter its expression, and thus influence the function of the encoded protein.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have indicated significant associations between collagen type IX and spinal and articular diseases (Matsui et al, 2004;Matsui, 2006;Hyun et al, 2011). It has been reported that mice homozygous or heterozygous null for COL9A2 exhibit articular cartilage degeneration (Brachvogel et al, 2013). As yet, the role of COL9A2 polymorphisms in the development of intervertebral disc disease in the Chinese population has not been reported.…”
Section: Introductionmentioning
confidence: 95%